A peptide-based biological coating for enhanced corrosion resistance of titanium alloy biomaterials in chloride-containing fluids. (March 2017) - Muruve, Noah; Feng, Yuanchao; Platnich, Jaye; Hassett, Daniel; Irvin, Randall; Muruve, Daniel; Cheng, Frank
Titanium alloys are common materials in the manufacturing of dental and orthopedic implants. Although these materials exhibit excellent biocompatibility, corrosion in response to biological fluids can impact prosthesis performance and longevity. In this work, a PEGylated metal binding peptide (D-K122-4-PEG), derived from bacteria Pseudomonas aeruginosa, was applied on a titanium (Ti) alloy, and the corrosion resistance of the coated alloy specimen was investigated in simulated chloride-containing physiological fluids by electrochemical impedance spectroscopy and micro-electrochemical measurements, surface characterization, and biocompatibility testing. Compared to uncoated specimen, the D-K122-4-PEG-coated Ti alloy demonstrates decreased corrosion current density without affecting the natural passivity. Morphological analysis using atomic force microscopy and scanning electron microscopy confirms a reduction in surface roughness of the coated specimens in the fluids. The D-K122-4-PEG does not affect the binding of HEK-293T cells to the surface of unpolished Ti alloy, nor does it increase the leukocyte activation properties of the metal. D-K122-4-PEG represents a promising coating to enhance the corrosion resistance of Ti alloys in physiological fluids, while maintaining an excellent biocompatibility.